ABOUT BLOCKCHAIN TECHNOLOGY AND THE SECURITY OF ELECTRONIC PAYMENTS: COMBATING INTERNET FRAUD IN KAZAKHSTAN (Journal of actual problems of jurisprudence, 2026)
How can the law keep pace with the rapid development of technologies that are fundamentally transforming financial transactions? This article addresses this question by examining the role of blockchain in securing electronic payments and combating cyber fraud within the legal framework of Kazakhstan. The analysis traces distributed ledger technology from its cryptographic foundations to regulatory approaches across three jurisdictions — the European Union, the United Arab Emirates, and Kazakhstan itself.Drawing on cybercrime statistics from 2024–2025 and emerging case law, the study identifies a central contradiction: the decentralised nature of blockchain conflicts with legal frameworks built around identifiable intermediaries.The findings point to what may be termed a «presumption of transaction authenticity» — an innovative evidentiary concept underpinned by cryptographic verification. However, significant obstacles remain. Courts lack clear guidelines regarding the admissibility of blockchain-based evidence. Liability norms do not accommodate distributed systems where no single party exercises unilateral control over the ledger. Anti-money laundering requirements clash with pseudonymous transactions.The article concludes by proposing specific amendments to Kazakhstan’s payment legislation, arguing that the digital tenge pilot project and the AIFC regulatory sandbox position the country as a regional leader in blockchain regulation — provided the legislature takes decisive action to address the identified gaps.Keywords: blockchain, electronic payments, smart contracts, cybercrime, digital jurisdiction, AIFC, regulatory sandbox, Digital Tenge, KYC/AML, MiCA.